FAKTOR YANG BERPENGARUH TERHADAP KENAIKAN BERAT BADAN IBU HAMIL KEKURANGAN ENERGI KRONIS DI PUSKESMAS RALLA KABUPATEN BARRU - Rismawati Rismawati; Wirawati Amin; Marhaeni Marhaeni; Indriani Indriani (Sekolah Tinggi Pariwisata Mataram, 2022)
Chronic energy deficiency (KEK) is a condition in which a person's nutritional status is poor due to a lack of consumption of food sources of energy containing macronutrients that lasts for a long time or are chronic. A person is said to be suffering from Chronic Energy Deficiency when the LILA (upper arm circumference) is < 23.5 cm. To find out the factors that influence the weight gain of pregnant women with Chronic Energy Deficiency (KEK) at the Ralla Health Center. The method used in this research is an analytical survey with a cross sectional approach. The population in this study were all pregnant women with chronic energy deficiency as many as 73 respondents and a sample of 34 respondents. This research was conducted in February-May 2021 using a data collection format.The results of the univariate analysis showed that of the 34 respondents who stated the role of the midwife in the good category were 32 people (94.1%) and who stated the role of the midwife in the sufficient category were 2 people (5.9%), there were 32 respondents (94.1%). have good motivation and 2 respondents (5.9%) have less motivation. Bivariate results show the role of midwives with a P value = 0.05, motivation with a p value = 0.05. It can be concluded that the role of midwives and motivation has a relationship which means that it affects the weight gain of pregnant women with Chronic Energy Deficiency. The need for counseling about the importance of eating nutritious foods in order to increase weight in pregnant women with Chronic Energy Deficiency.